2016
DOI: 10.1093/europace/euw084
|View full text |Cite
|
Sign up to set email alerts
|

Data mining experiments on the Angiotensin II-Antagonist in Paroxysmal Atrial Fibrillation (ANTIPAF-AFNET 2) trial: ‘exposing the invisible’

Abstract: With the ANTIPAF-AFNET 2 dataset, the present data-mining analyses suggest that a baseline SF-12 mental component score, age, systolic blood pressure, BUN, and creatinine level of the patients are predictors of AF burden. Additional studies are necessary to understand the distinct kidney-specific pathophysiological pathways that contribute to AF burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In addition, BUN and Cr levels were higher in the PoAF (+) group (P = .007 and P = .043, respectively). Renal insufficiency (RI) paves the way for many other diseases that can threaten the patient's life, although studies also have shown that RI alone may result in the development of AF [Okutucu 2017]. This can be attributed to the electrolyte imbalance that occurs in RI, acid-base disturbances, hypertension, and left atrial and left ventricular dilation occurring in time in patients with RI [Allison 2013].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BUN and Cr levels were higher in the PoAF (+) group (P = .007 and P = .043, respectively). Renal insufficiency (RI) paves the way for many other diseases that can threaten the patient's life, although studies also have shown that RI alone may result in the development of AF [Okutucu 2017]. This can be attributed to the electrolyte imbalance that occurs in RI, acid-base disturbances, hypertension, and left atrial and left ventricular dilation occurring in time in patients with RI [Allison 2013].…”
Section: Discussionmentioning
confidence: 99%
“…Valid arguments were theoretically and empirically supplied as to why AUC should be preferred over accuracy, which is merely a ratio of correctly predicted results to the total number of instances examined. 19,20 A higher value of AUC for a parameter is an indication of its higher relevance in determining the class label. Since RIMARC algorithm aims to maximize the AUC value directly, it outperforms the other data mining algorithms on average, with a statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“… 133 AI has been applied to electronic health records to reduce spurious AF alerts, using natural language processing and CHA2DS2-VASc elements, providing 98% accuracy and reducing workload by 84%. 134 AI of clinical data predicted sinus rhythm after electrical cardioversion of AF, 135 and after guideline-directed medical therapy 136 in secondary analyses of the Flec-SL-AFNET 3 and ANTIPAF-AFNET 2 trials, respectively. Neural network classifiers can predict recurrent syncope from patients in the emergency room using the history and ECG with accuracies from 67 to 95%.…”
Section: Artificial Intelligencementioning
confidence: 99%